A new species of Camellia L. (Theaceae) from south-central of Vietnam: evidence from morphology and anatomy analyses - Nguyen, van Canh; Tran, Thi Thuy Nhan; Luong, van Dung; Phan-Thi, Thanh Nha; Phan, Le Y; Nguyen, Thi Lien Thuong; Truong, Quang Cuong; Nguyen, Quoc Bao; Truong, Ba Vuong (Phytotaxa, 2026)
A new species of Camellia (section Piquetia) from south-central of Vietnam is described. Within section Piquetia, the new species is most similar to C. honbaensis, but differs in several morphological traits (smaller leaves, longer reddish pedicels, glabrous stamens, and styles completely free from the base). This study provides a standard taxonomic description, together with morphological comparisons between the new species, Camellia honbaensis, with other similar species and additional information on the species habitat, estimated conservation status, and the anatomy of its leaves and branches.